Pengaruh Stres Kerja Terhadap Produktivitas Kerja Pegawai Badan Pusat Statistik - Nurmila Rahayaan; Alexander Phuk Tjilen; Hesty Tambajong (Department of State Administration - Musamus University, 2019)
Work stress is a problem that currently becomes a conversation and its position is very important because it relates to work productivity. The progress of the organization relies heavily on the ups and downs of its employees ' work productivity. Therefore, the influence of the two becomes an interesting thing to be examined. This research aims to find out how much work stress affects the working productivity of the employees Central agency of Merauke District. This type of research is quantitative with sampling technique i.e. total sampling. Data processing using SPSS application version 23. The results showed that there was a significant and positive influence between working stress on the work productivity of the central Statistic agency of Merauke district. From the correlation analysis done, the strength of the influence between the two variables is in the medium category (0.407) with the donation of impact variable work stress to the working productivity variable by 16.6%. The remainder (83.4%), employee work productivity of the District Central Statistics of Merauke regency was influenced by other variables not examined in the study. Work stress experienced by employees of Central Agency Statistics Merauke District is in the low category with the productivity of high-generated work. This is due to the employees of the Central Statistics Agency Merauke District can conduct self-control of the stress experienced, has a high motivation and work and loyalty and has familiarize themselves with the demands of the work So.